PENDAMPINGAN PSYCHOLOGICAL FIRST AID (PFA) DAN PLAY THERAPY PADA KORBAN BANJIR DI DESA PAYAMAN - Khasan, Mohammad; Faqihuddin, Ahmad; Umi Sholihah, Kholifah; Natalia Susanti, Ruth (Universitas katolik Musi Charitas, 2023)
Floods in Payaman Village, especially Karanganyar Hamlet at the end of 2022 and early 2023(December 31 2022 to January 2, 2023) had an impact on infrastructure, materials, and theconditions of the people in the area. Data from the Kudus Disaster Management Agency (BPBD)found that the floods affected 246 hectares of paddy fields, 310 families (KK) with details of1,190 people, while the victims who were displaced were 14 families with details of 33 peopleconsisting of 10 adults, 8 elderly, 4 toddlers, and 11 children. The hit flood caused the emergenceof problems. The situation resulted not only material losses but also mental health problems ofthose who stayed in refugee camps. Hence, the Faculty of Psychology, Muria Kudus University(UMK) in collaboration with Payaman Village carried out Psychological First Aid (PFA)activities for adult refugees and play therapy for children in refugee camps. This activityincluded the fourth phase of disaster management, namely post-disaster recovery, which wascarried out one day on January 9, 2023. This program helped children to be happier and moreactive in moving. Likewise, adult refugees seem more relieved after participating in PFA becausethey have shared disturbing feelings and thoughts. Lastly, stakeholders may provide similarprogram which is sustainable to improve mental health conditions of disaster victims.